The Catholic Communities of the Aegean Archipelago during the Greek Revolution, 1821–1830 - Kousouris, Dimitris (Historein, 2022)
The Catholics of the Aegean islands represent a rather neglected subject in the story of the Greek War of Independence. As these communities enjoyed a large degree of autonomy from the Sublime Porte, were under French protection and participated in the global network of the Catholic Church, their integration into the Greek state was difficult. The frictions between insurgents and island Latins, the attempts of the Greek government to impose its authority, the efforts of those communities to mobilise their regional and international networks in order to maintain autonomy and their ultimate acceptance of the description “Greeks of the Western Church” attributed to them by the insurgents demonstrates that the making of the Greek nation was an open-ended process, providing valuable insights into the transition from a prenational/extraterritorial conception of sovereignty to a national/territorial one.